Strategic Management Accounting as a Decision-Making Tool in the Era of Technological Disruption - Fitri Sukmawati; Muhammad Ali (PT. Hafasy Dwi Nawasena, 2026)
Technological disruption, characterized by the rapid development of digitalization, big data, and integrated information systems, has transformed the business environment and demanded increasingly complex managerial decision-making. This situation has significant implications for the role of management accounting, which is no longer limited to recording and controlling costs but has evolved into a strategic instrument to support decision-making. This article aims to conceptually analyze the role of strategic management accounting as a decision-making tool in the era of technological disruption based on a literature review. The research method used is a qualitative approach with a descriptive-analytical design through a literature review, analyzing relevant theories, concepts, and previous research findings. The focus of the analysis is directed at the transformation of the role of strategic management accounting in providing strategically valuable financial and non-financial information for management. The results of the study indicate that conceptually, strategic management accounting has an important contribution in improving the quality of decision-making through the integration of technology, data analysis, and a long-term orientation towards organizational competitive advantage. This article is expected to enrich the theoretical study of management accounting and provide conceptual implications for the development of managerial decision-making practices in the era of technological disruption.